Соціальна диференціація в системі чинників сприяння та протидії активізації інноваційної праці - Семикіна, М.В.; Жеребченко, Т.І. (Стратегія і механізми регулювання промислового розвитку, 2013)
Розглянуто соціальну диференціацію в системі чинників сприяння та протидії активізації інноваційної праці, зосереджено увагу на визначенні системи чинників впливу на працю. Проаналізовано фактори впливу на активізацію інноваційної праці та доведено необхідність створення механізму стимулювання праці. Рассмотрена социальная дифференциация в системе факторов содействия и противодействия активизации инновационной работы, сосредоточено внимание на определении системы факторов влияния на работу. Проанализированы факторы влияния на активизацию инновационной работы и доказана необходимость создания механизма стимулирования труда. The issues associated with the installation of additional payments to teachers and incentive bonuses, their size are not within the jurisdiction of the school: the expenditure are under a public institution control, CEI has autonomous authority to establish direct spending. Appropriations for salaries are approved within the established State Budget of Ukraine, which is calculated, being locally based on staff. All budget funds are earmarked and expended in accordance with the approved budget expenditures for the relevant fiscal year. This raises the question of an effective system of incentives aimed at boosting the research and innovation combined with scientific and educational components of teacher CEI and decent pay, regardless of “regional” employment. Professional is a teacher, a person who presents a significant social society profession, worked out by the long-term evolutionary development, is now focused on the ability of their implementation to a wide audience of student contingent, on the one hand, and the need to meet the social demands of today, on the other hand, requiring teacher as a representative of the same profession as organizing work with pupils audience in need of motivation of action, therefore, adequate for the complex stimulation. The promotion of employment of employees of secondary schools by means of their certification by raising the personal level,of course, raises the quality of educational services through theoretical generalization of laws and theories as a consequence (result) of the development of new knowledge. The stimulating effect of certification also provides the creation of a direct link between the outcome and the size of the salary. Given the above, we note that the new economic conditions prevailing in the country, require systemic organizational performance and improvement of forms of management, touching all areas of management, including the education sector, to work which the teachers are involved. The lack of unified conceptual foundations of education, systematic non-compliance with applicable legislation regulating relations in the sphere of education cause the decline in the prestige of the teaching profession. The mechanism should developed that is aimed at making the teaching profession so that it would impose on them duties, more socially significant than any other profession, would create a suitable environment for them that would be consistent with both their professional quality and social requirements or the performance of professional duties. The mechanism proposes to achieve this goal mechanism allows a confluence of social needs assessment results of teachers to apply appropriate incentives in relation to a person as a teacher and to his disciples, enabling incentives, however, self-development teacher and his efforts on the development of students as future members of society.